Synergy of Information Technology, Accounting Information Systems, and Human Resource Quality in Enhancing Employee Performance - Moh Ali Wafa; Dewi Kusmayasari; Irawan, Mohamad Rizal; Darmayanti, Novi (The Journal of Financial, Accounting, and Economics, 2025)
This study aims to analyze the influence of the use of information technology, accounting information systems, and human resource quality on employee performance at PT Sinar Mutiara Miru-Lamongan. The method used in this study is a quantitative descriptive approach with a population of all company employees. The data used consists of primary data obtained through questionnaires, as well as secondary data to support the analysis. The data processing was carried out using SPSS version 25 software, through the stages of descriptive statistical tests, data quality tests, classical assumption tests, and hypothesis tests. The results of the study indicate that simultaneously, the use of information technology, accounting information systems, and the quality of human resources significantly influence employee performance. Partially, each variable also proved to have a significant impact, with human resource quality being the most dominant factor influencing performance. These findings indicate that improving HR competency, supported by an integrated information system and appropriate technology utilization, will drive optimal work productivity. This research provides a practical contribution to companies in formulating performance improvement strategies based on the synergy between technology, information systems, and HR development.